Scottish Presbyterians and the Act of Union 1707 - Stephen, Jeffrey, Dr (Edinburgh University Press, 2007)
Set against the background of post-revolution Scottish ecclesiastical politics, this book addresses the hitherto largely neglected religious dimension to the debates on Anglo-Scottish Union. Focusing predominantly on the period between April 1706 and January 1707, the book examines the attitudes and reactions of Presbyterians to the treaty and challenges many of the widely held assumptions about the role of the church and other groups during the debate. The focal point of the Kirk's response was the Commission of the General Assembly. Through the extensive use of church records and other primary sources the work of the commission in pursuit of church security through its debates, committees and addresses, is discussed at length. The book also examines the church and groups like the Cameronians and Hebronites in relation to the parliamentary debate, the pursuit of alternatives to incorporation, popular protest, addressing and armed resistance.